SEROEPIDEMIOLOGI OF SEPTICHAEMIA EPIZOOTICA BY GENDER IN BALI CATTLE IN SUMBAWA - Besung, I Nengah Kerta; Suarjana, I Gusti Ketut; Tono PG, Ketut; Suwiti, Ni Ketut (Buletin Veteriner Udayana, 2017)
This study aims to determine the distribution map Septicaemiaepizootica (SE) by gender in Dompu, Bima and Sumbawa. A total of 240 serum samples derived from three districts in West Nusa Tenggara used the study sample. Serum was tested by ELISA (Enzyme Linked Immunosorbent Assay). Data samples positive and negative SE, presented descriptively. The results showed that seropositive SE at 18% bulls and cows by 12%. It can be concluded that the incidence of SE in the bulls higher than cows.
Keywords: Septicaemia epizootica; Nusa Tenggara Barat; sapi; West Nusa Tenggara, cattle